L'elevage au Mali central: La structure des troupeaux avec quelques parametres demographiques relatifs - Wilson, R.T. (CIPEA, 1980)
Studies the flock and herd structure of sheep, goats, cattle, equines and camels in Mali and provides information on related parameters for traditional systems in order to understand the management and production characteristics of these species.